"I Went to Singapore and I Didn't Understand their English": A Portrait of Five International Islamic Boarding School Teachers on Global Englishes - Fikri, Moh. Hilman; Wahyu Sudrajad; Henti Cerdik Susanti Waruwu; Ervan Pramudyanto (International Journal of English and Applied Linguistics (IJEAL), 2025)
Myriads of previous endeavours on constructing English language learning identity have been directed worldwide. The study predominantly focuses on constructing teacher identity in English language learning in general. It does not explicitly discuss the massive development of the English language (Global English). Therefore, to fill the lacuna, the current study will focus on five International Islamic boarding school teachers, concerning the globalization of English. The current study will be an engaging narrative to explore and investigate, considering that the recruitment of five international Islamic boarding school teachers in Malang will pose a dilemma and provide a true reflection of the ongoing global debate regarding the globalization of English (GE). In-depth interviews and observations were administered to collect the data. The data would then be analysed under Braun's & Clarke's thematic analysis (2006). The data were then identified to produce a data transcript. After transcribing the data, the researcher frequently read the transcript to highlight the interview data and create the identifying themes. Finally, the researchers concluded the interview data. Moreover, the study generated three analysis themes (orientation, adjustment, and identity construction). In the orientation, the subjects believed that the teacher should tolerate the students' errors in practising the language to avoid deterring students from studying the language. Moreover, after experiencing the development of English, Nana, Hana, Miya, Layla, and Mila (pseudonyms) suggested that they would still accentuate the teaching of Standard English, with a high tolerance to retain students’ high motivation. Finally, in the theme of identity construction, they believed that the students should skew their preferences towards standard English to sound more sophisticated in a formal context